Impact of the economic crisis on the apple production price in the Republic of North Macedonia - Lazo DIMITROV and Viktor GJamovski and Despina Popovska Stojanov and Marija GJOSHEVA KOVACHEVIKJ (Radovi Poljoprivredno-prehrambenog fakulteta Univerziteta u Sarajevu, God. LXVII, broj 72/2, Works of the Faculty of Agriculture and Food Sciences, University of Sarajevo, 2022)
Apple production has the greatest significance among all types of fruit crops in Macedonia, sharing 56% of the total fruit production. Due to the economic crisis caused by Covid-19 and the war in Ukraine, the prices of agricultural inputs have increased greatly. To that end, the main goal of this paper is to evaluate the impact of the global economic crisis on the apple production price. The production costs calculation is based on calculation of variable and fixed costs of apple production for 2020 and 2021 as reference years and 2022 as the year when the production price change is considered. Data for the normative calculation and production price for 2020 and 2021 are obtained based on the expert knowledge and confirmed with the semi-structured interview with 3 farmers and 2 apple producing companies. Based on this normative calculation and market prices for inputs in 2020, 2021 and 2022 collected from the 10 input suppliers, AMIS and SSO, the apple production price is calculated. The results show that the economic crisis has a large negative economic impact on apple production, as the estimated full production price of apples in 2022 ha increased by 37% compared with that of 2020 & 2021.
Keywords: impact assessment, socio-economic crisis, apple producers, production price, production costs.